A simple force and deformation analysis of deep hole gundrilling - Chan, Huazhi (2014)
Workpiece deformation, short tool life and poor surface finish are challenges in the gundrilling of Inconel 718. This study was carried out to gain insights into the associated force and deformation behavior. Experimental analysis on hole deflection, tool edge forces and workpiece residual stresses were performed. Finite element simulations were also carried out to simulate the gundrilling of a workpiece section. Hole deflection was found to occur towards thinner workpiece material. In addition, shear and normal forces acting on the workpiece hole wall were found to be responsible for deformation of hole cross sectional geometry. Conclusions drawn from this study could contribute towards developing future solutions to address machinability issues.